Prosecuting Congolese war crimes - Tsabora, James (Taylor and Francis (Routledge), 2014)
In August 2010, the United Nations Office of the High Commissioner for Human Rights (OHCHR) published a Mapping Exercise Report (MER) documenting serious violations of human rights and international humanitarian law during the Democratic Republic of Congo (DRC) conflicts between 1993 and 2003. The Report relied on various reports of the United Nations (UN) Secretary-General, reports of the United Nations Mission in Congo (MONUC), reports of the UN Panel of Experts on the Illegal Exploitation of Natural resources and Other Forms of Wealth in the DRC, and also reports by nongovernmental organizations (NGOs) such as Human Rights Watch, Amnesty International, M´edecins Sans Fronti`eres, GlobalWitness, and International Peace Information Service (IPIS). In addition to giving an overview of the main features of the DRC conflicts from a human rights perspective, the MER (Report) also gave particular focus on the commission of serious crimes of international concern such as war crimes, crimes against humanity, and possible instances of genocide during the conflicts, particularly in the period between 1997 and 2003.